2011
DOI: 10.1371/journal.pone.0025926
|View full text |Cite
|
Sign up to set email alerts
|

A Laminin G-EGF-Laminin G Module in Neurexin IV Is Essential for the Apico-Lateral Localization of Contactin and Organization of Septate Junctions

Abstract: Septate junctions (SJs) display a unique ultrastructural morphology with ladder-like electron densities that are conserved through evolution. Genetic and molecular analyses have identified a highly conserved core complex of SJ proteins consisting of three cell adhesion molecules Neurexin IV, Contactin, and Neuroglian, which interact with the cytoskeletal FERM domain protein Coracle. How these individual proteins interact to form the septal arrays that create the paracellular barrier is poorly understood. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Subperineurial glia express the cell-adhesion molecule Neurexin IV (NrxIV), a structural component of septate junctions required for the proper establishment of the blood-brain barrier ( Banerjee et al, 2011 ; Banerjee et al, 2006 ; Baumgartner et al, 1996 ; Stork et al, 2008 ). Antibody staining against NrxIV on Flybow clones of ePG4, ePG7 and ePG10 confirms their subperineurial identity ( supplementary material Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Subperineurial glia express the cell-adhesion molecule Neurexin IV (NrxIV), a structural component of septate junctions required for the proper establishment of the blood-brain barrier ( Banerjee et al, 2011 ; Banerjee et al, 2006 ; Baumgartner et al, 1996 ; Stork et al, 2008 ). Antibody staining against NrxIV on Flybow clones of ePG4, ePG7 and ePG10 confirms their subperineurial identity ( supplementary material Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For immunoblotting and immunostaining, standard procedures were used (Banerjee et al, 2011). Primary antibodies used were: guinea pig anti-Ringer (1:3000), anti-FasII [Developmental Studies Hybridoma Bank (DSHB), 1:500], anti-ELAV (DSHB, 1:500), anti-Wrap (Wheeler et al, 2009), anti-Slit (DSHB, 1:250), anti-GFP (Life Technologies, 1:500), anti-β-Gal (Promega, 1:500), anti-acetylated-Tubulin (Sigma T7451 and T6793, 1:2000) and anti-α-Tubulin (DSHB, 1:50,000).…”
Section: Ringer Antibody Generation Immunostaining and Immunoblottingmentioning
confidence: 99%
“…1A). Because CNTNAP2 contains a so-called "neurexin repeat" (LNS-EGF-LNS), it has been suggested that CNTNAPs are members of the neurexin family of synaptic cell adhesion molecules (25,26). CNTN2 consists of six Ig domains followed by four fibronectin domains, and it is tethered to the cell surface by a glycosylphosphatidylinositol anchor (Fig.…”
mentioning
confidence: 99%